Progress in the symptom cluster management of patients with Crohn's disease (克罗恩病患者症状群管理研究进展) - LU Hui (陆慧); WU Xiaoyan (武筱燕); YU Meiling (余美玲) (Association of Integrative Nursing, 2024)
Crohn's disease is a type of inflammatory bowel disease (IBD). Its symptom cluster can damage patients' psychical and psychological health. It is required to enhance the symptom cluster management of patients with Crohn's disease. In this paper, the concept of symptom cluster, assessment tools of symptom cluster and intervention of symptom cluster were summarized to enlighten the future research direction and clinical nursing practice, aiming to provide reference for symptom cluster management and nursing of patients with Crohn's disease. (克罗恩病是一种常见的胃肠道慢性炎症性疾病, 克罗恩病症状群严重影响患者的身心健康和生活质量。因此, 加强克罗恩病患者症状群的管理是十分必要的。本研究就症状群的概念、克罗恩病症状群评估工具以及症状群干预等方面的现状进行总结和分析, 旨在为制定克罗恩病患者的症状群管理方案和护理工作提供参考。)